HUBUNGAN PERAN PETUGAS KESEHATAN DAN PAPARAN MEDIA TERHADAP PEMBERIAN PASI OLEH IBU YANG MEMILIKI BAYI USIA 0-6 BULAN DI KELURAHAN PEMATANG KAPAU PEKANBARU - Mona Dewi Utari; Ihsan Suheimi (Ensiklopedia of Journal, 2023)
PASI stands for BMS and generally in the form of infant formula. Currently one - only instant baby food that is generally acceptable formula. Formula feeding experience and level of practicality is different from breastfeeding. Breast-fed infants, breastfed more often than formula-fed. When the baby is formula-fed, usually no concern whether he gets enough milk. Formula feeding remains a part of the culture of parenting a baby. In this study the method used is by way of cross sectional analytic approach. The number of samples that is 50 people, with a total sampling . The research was conducted on May 8 and May 10, 2014 with the goal of research mothers who have infants aged 0-6 months and give PASI. Data were collected by questionnaires using interview techniques. Data processing uses the univariate and bivariate analyzes (Chi-Square). Univariate results indicate that the role of health workers towards giving the majority a PASI 30 (60%). The amount of media exposure that affects the majority of the administration of a PASI 29 (58%), the amount of the provision PASI with mothers who have a high desire that some 25 people (50%). The results of bivariate analysis showed that p-value <α = 0.05 ie, p-value = 0.021 <0.05 it can be concluded that there is a relationship role to the provision of health care workers PASI in infants aged 0-6 months in Pekanbaru Pematang Kapau village. And p-value = 0.010 <0.05 so no relation to the provision of PASI media exposure in infants aged 0-6 months in Pekanbaru Pematang Kapau village.